Structural and Functional Alterations Caused by Aureobasidin A in Clinical Resistant Strains of Candida spp. - Rodrigo Rollin-Pinheiro; Daniel Clemente de Moraes; Brayan Bayona-Pacheco; Jose Alexandre da Rocha Curvelo; Giulia Maria Pires dos Santos-Freitas; Mariana Ingrid Dutra da Silva Xisto; Luana Pereira Borba-Santos; Sonia Rozental; Antonio Ferreira-Pereira; Eliana Barreto-Bergter (Journal of Fungi, 2023)
Candida species are one of the most concerning causative agents of fungal infections in humans. The treatment of invasive Candida infections is based on the use of fluconazole, but the emergence of resistant isolates has been an increasing concern which has led to the study of alternative drugs with antifungal activity. Sphingolipids have been considered a promising target due to their roles in fungal growth and virulence. Inhibitors of the sphingolipid biosynthetic pathway have been described to display antifungal properties, such as myriocin and aureobasidin A, which are active against resistant Candida isolates. In the present study, aureobasidin A did not display antibiofilm activity nor synergism with amphotericin B, but its combination with fluconazole was effective against Candida biofilms and protected the host in an in vivo infection model. Alterations in treated cells revealed increased oxidative stress, reduced mitochondrial membrane potential and chitin content, as well as altered morphology, enhanced DNA leakage and a greater susceptibility to sodium dodecyl sulphate (SDS). In addition, it seems to inhibit the efflux pump CaCdr2p. All these data contribute to elucidating the role of aureobasidin A on fungal cells, especially evidencing its promising use in clinical resistant isolates of Candida species.